Development of Novel Functional Materials for the Manufacture of Electronic and Optoelectronic Devices (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Interest in functional materials is rapidly growing, owing to their potential uses across a broad range of fundamental and applied areas of application such as in electronic and optoelectronic devices. A large variety of platforms based on functional materials have been used to demonstrate unique and useful properties that go beyond what is possible with conventional photonics and electronics. The related discoveries and techniques have stimulated wide-ranging applications in microelectronics, solar cells, spectroscopy, microscopy, biochemistry, and so forth. This Special Issue aims to provide a comprehensive overview of the state-of-the-art development of novel functional materials for the manufacture of electronic and optoelectronic devices, and to stimulate new interest in this field. Topics covered in this collection include, but are not limited to, functional-material-related nanofabrications, nanostructures, and electronic and optoelectronic devices, which will provide great help and inspiration to researchers engaged in related fields.